The effect of servant leadership and non-physical work environment on employee performance with motivation as mediation at the nusakambangan open correctional institution - Peri Wahyono; Siti Nur Azizah (Jurnal Mantik, 2026)
The aim of this research is to examine the influence of the non-physical work environment and servant leadership on employee performance in the Nusakambangan open prison, with motivation as a mediating variable. Servant leadership emphasizes a leadership style that prioritizes service to subordinates, while the non-physical work environment includes psychological and social aspects that can affect employee comfort and productivity. This descriptive study used a quantitative approach. This study involved 68 people working at the Nusakambangan Open Prison. Sampling saturation was used to cover the entire population, consisting of 68 employees. In this study, interviews, observations, and questionnaires were used to collect data. Structural Equation Modeling (SEM) or Partial Least Squares (PLS) was used to conduct data analysis. The research findings indicate that servant leadership has an impact on motivation, as does the non-physical work environment; both affect performance through motivational mediation. The results suggest that a leadership style that prioritizes service and a psychologically supportive work environment can increase employee motivation, which in turn can lead to better performance.